Pricing the passages related to traffic restriction by using novel genetic algorithms. (8th February 2022) - Darroudi, Farzaneh; Ala, Ali; Attari, Mahdi Yousefi Nejad
Nowadays, a lot of transport-related data for traffic modelling are available. Many measures have been taken, which can be referred to as pricing related to traffic restrictions. Amongst the most critical problems in traffic, the plan is deciding the best price. Therefore, in this article, we have tried to use the genetic algorithm as one of the meta-heuristic algorithms and admit more agents and classification on users, vehicles, and the combination of techniques applied in earlier investigations, an effective measure to reduce and control traffic in busy thoroughfares. Also, the evaluation approach estimates the costs of traffic routes determined with the Frank-Wolfe algorithm, modified to examine intersection progress and delays. Intersections are modelled with genetic algorithms and the methods used for choosing the optimal schedule of project improvements. The sensitivity study outcomes and analysis of the various assumptions indicate how Taguchi and model parameters affect the model's performance and algorithm.